Manuscript, print, and the English Renaissance lyric - Marotti, Arthur F., 1940- (Cornell University Press, 1995)
The last of the literary genres to be incorporated into print culture, verse in the English Renaissance not only was published in anthologies, pamphlets, and folio editions, it was also circulated in manuscript. In this ground-breaking historical and cultural study of sixteenth- and early seventeenth-century lyric poetry, Marotti examines the interrelationship between the two systems of literary transmission and shows how in England manuscript and print publication together shaped the emerging institution of literature. Surveying a wide range of manuscript and print poetry of the period, Marotti outlines the different social and institutional contexts in which poems were collected and transmitted. He focuses on the two kinds of verse that were circulated more commonly in manuscript than in print - the obscene and the political - and he considers the contributions of scribes and compilers, particularly in composing "answer poetry" and other verse. Analyzing the process through which print gradually replaced manuscript as the standard medium for lyric verse, he identifies four crucial events in the history of publication in England: the appearances of Tottel's Miscellany ( (1557), Sir Philip Sidney's works in the 1590s, Ben Jonson's folio Workes (1616), and the posthumous editions of the poems of Donne and of Herbert (both 1633). Marotti also considers how certain material features of the book determined the reception of poetry, and he explores how poets attempted to establish their authority in print in relation to publishers, patrons, and readers.